2016
DOI: 10.1038/srep39199
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an evolutionary conserved structural loop that is required for the enzymatic and biological function of tryptophan 2,3-dioxygenase

Abstract: The enzyme TDO (tryptophan 2,3-dioxygenase; TDO-2 in Caenorhabditis elegans) is a potential therapeutic target to cancer but is also thought to regulate proteotoxic events seen in the progression of neurodegenerative diseases. To better understand its function and develop specific compounds that target TDO we need to understand the structure of this molecule. In C. elegans we compared multiple different CRISPR/Cas9-induced tdo-2 deletion mutants and identified a motif of three amino acids (PLD) that is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…For example, the tryptophan‐converting enzyme tryptophan 2,3‐dioxygenase (TDO‐2) was identified in cluster C18, showing an increasing abundance during development. In support of our data showing an increased abundance of TDO‐2 during larval development, TDO‐2 has been shown previously to regulate adult life span and motility during ageing, and it has an age‐accumulative effect in regulating motility . In addition, we found that protein groups that tended to decrease in abundance during development were mainly associated with the actin cytoskeleton and cell cycle regulation.…”
supporting
confidence: 90%
“…For example, the tryptophan‐converting enzyme tryptophan 2,3‐dioxygenase (TDO‐2) was identified in cluster C18, showing an increasing abundance during development. In support of our data showing an increased abundance of TDO‐2 during larval development, TDO‐2 has been shown previously to regulate adult life span and motility during ageing, and it has an age‐accumulative effect in regulating motility . In addition, we found that protein groups that tended to decrease in abundance during development were mainly associated with the actin cytoskeleton and cell cycle regulation.…”
supporting
confidence: 90%
“…Its heme group is present as an inactive Fe 3+ form that needs to be changed to Fe 2+ form to be active24. Furthermore, TDO is mainly found as homodimers that can transform to active tetramers of ∼190 kDa in eukaryotes and ∼120 kDa in prokaryotes 27, 33. Lewis-Ballester et al 34 found a binding site for L-Trp in hTDO that did not influence enzyme catalysis but can block the degradation of hTDO, revealing a new L-Trp-mediated regulation mechanism for cellular hTDO degradation.…”
Section: Enzymes Involved In the Kyn Pathway: Ido And Tdomentioning
confidence: 99%
“…Lewis-Ballester et al 34 found a binding site for L-Trp in hTDO that did not influence enzyme catalysis but can block the degradation of hTDO, revealing a new L-Trp-mediated regulation mechanism for cellular hTDO degradation. Additionally, Michels et al 33 found that three amino acid residues, TDO-2 (ΔPLD), TDO-2 (del), and TDO-2 (del B), were vital for the enzymatic activity of TDO.…”
Section: Enzymes Involved In the Kyn Pathway: Ido And Tdomentioning
confidence: 99%
“…TDO is a tetrameric complex containing a heme that is important for tryptophan oxidation (Capece et al, 2010). Three highly conserved loops are required for binding the heminic cofactor and for the induced-fit mechanism involved in binding tryptophan (Huang et al, 2013;Michels et al, 2016). Information on conserved sequences, structures and mechanisms are of great importance in the synthesis of new inhibitors of this enzymatic step (Huang et al, 2013;Michels et al, 2016).…”
Section: (4) Enzymes Of the Tryptophan→ommochrome Pathwaymentioning
confidence: 99%
“…Three highly conserved loops are required for binding the heminic cofactor and for the induced‐fit mechanism involved in binding tryptophan (Huang et al, ; Michels et al, ). Information on conserved sequences, structures and mechanisms are of great importance in the synthesis of new inhibitors of this enzymatic step (Huang et al, ; Michels et al, ). Hence, crystallographic data are needed if one intends to inhibit enzymes in both non‐model organisms and model organisms for which no tryptophan pathway mutants are available.…”
Section: Ommochrome Biochemistry: From the Indole To The Phenoxazone mentioning
confidence: 99%